Mechanical strength and intracellular uptake of CaCO3-templated LbL capsules composed of biodegradable polyelectrolytes: The influence of the number of layers - Palankar, Raghavendra; Pinchasik, Bat-El; Schmidt, Stephan; De Geest, Bruno G.; Fery, Andreas; Moehwald, Helmuth; Skirtach, Andre G.; Delcea, Mihaela (Journal of Materials Chemistry B, 2013)
Developing carriers comprised of biomaterials and capable of withstanding significant mechanical pressures, structural deformations and at the same time delivering biomolecules is of high interest for drug delivery. Using colloidal probe AFM combined with quantitative fluorescence microscopy, we investigated mechanical properties and release from CaCO3-templated polymeric capsules made of biodegradable polymers. The mechanical and release properties of these capsules were studied in comparison with those of CaCO 3-templated capsules composed of synthetic polymers. Furthermore, we assessed the influence of the number of polyelectrolyte LbL layers on the mechanical properties and release from biodegradable capsules. Mechanical deformation of capsules was studied upon intracellular uptake of these capsules. Based on these results, we discuss implications for the design of microcapsules. © The Royal Society of Chemistry 2013.
CRIS-Team Scopus Importer:2023-03-20